Enhanced Critical Size Defect Repair in Rabbit Mandible by Electrospun Gelatin/β-TCP Composite Nanofibrous Membranes. (1st June 2015) - Xu, Mingming; Zhang, Xuehui; Meng, Song; Dai, Xiaohan; Han, Bing; Deng, Xuliang
Abstract : The design and fabrication of biodegradable barrier membranes with satisfactory structure and composition remain a considerable challenge for periodontal tissue regeneration. We have developed a biomimetic nanofibrous membrane made from a composite of gelatin and β -tricalcium phosphate ( β -TCP). We previously confirmed the in vitro biological performance of the membrane material, but the efficacy of the membranes in promoting bone repair in situ has not yet been examined. Gelatin/ β -TCP composite nanofibers were fabricated by incorporation of 20 wt.% β -TCP nanoparticles into electrospun gelatin nanofibers. Electron microscopy showed that the composite membranes presented a nonwoven structure with an interconnected porous network and had a rough surface due to the β -TCP nanoparticles, which were distributed widely and uniformly throughout the gelatin-fiber matrix. The repair efficacy of rabbit mandible defects implanted with bone substitute (Bio-Oss) and covered with the gelatin/ β -TCP composite nanofibrous membrane was evaluated in comparison with pure gelatin nanofibrous membrane. Gross observation, histological examination, and immunohistochemical analysis showed that new bone formation and defect closure were significantly enhanced by the composite membranes compared to the pure gelatin ones. From these results, we conclude that nanofibrous gelatin/ β -TCP composite membranes could serve as effective barrier membranes for guided tissue regeneration.